Implementasi Strategi Digital Marketing untuk Penguatan Branding UMKM Lokal di Desa Dolok Kahean - Ricky Septian; Ahmad Afandi (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
Currently, MSMEs (Micro,Small,and Medium enterprises) face significant challenges, including minimal digital literacy,limited access to technology,and the need for appropriate branding strategy formulation to compete in the broadband era. This research is a community service program aimed at strengthening the skills and capacity of MSME actors in Dolok Kahean Village so that they can market their products online and build their brand through digital platforms. The method used is a qualitative-applicative approach focusing on intensive training, education, and assistance (hands-on). The material covered the mastery of basic digital marketing concepts, online brand management, and practical technical assistance in creating and managing social media accounts and e-commerse. The results indicate that the program successfully and effectively overcame digital literacy constraints and instilled awareness about the crucial need for fundamental changes in business mindset and models. Partners have mastered basic digital marketing concepts and were successfully assisted in creating an Instagram account, which tangibly strengthened their practical skills for expanding sales reach. Futhermore, the objective of strengthening branding was achieved, as partners recognize that branding is a vital investment and fundamental strategy for creating a solid foundation for long-term business sustainability. Overall, the implementation of digital marketing strategies proves to be a comprehensive solution that significantly aids the development of MSMEs in responding to the shift in consumer behavior toward online shopping.